Nuclear Data Sheets for A=51 - Wang, Jimin; Huang, Xiaolong (Nuclear data sheets, 2017)
The 2006 version of nuclear data sheets for A=51 (2006Hu10) has been revised and updated on the basis of the experimental results from various decay and reaction studies before March 2016. The experimental data for all known nuclei with mass number A=51 (Cl, Ar, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni) have been revised, updated, and incorporated into the ENSDF data file. The data sets of levels, gammas for 51Ca, 51Sc, 51Ti, 51Mn, and 51Fe are expanded. The experimental methods, references, Jπ arguments, and necessary comments are given in the text. In addition, Q values have been updated based on 2012Wa38.